Strategi Orang Tua Dalam Memotivasi Anak Untuk Shalat Berjamaah - Muhammad Fadel; Ahmad Rivauzi (Prodi Pendidikan Keagamaan Islam, 2022)
This study aims to determine the strategy of parents in motivating their children to pray in congregation at the mosque. This study uses a qualitative method with the type of field research. Researchers used data collection methods, namely interviews, observation, and documentation. Sources of data were taken through informants in which parents of children whose children pray regularly in the mosque and documents in the form of videos, photos, and other documents. The data analysis technique uses data reduction, data presentation, and drawing conclusions. In this study it was found that first, a good strategy to motivate children to pray in congregation at the mosque. Second, the supporting and inhibiting factors of parents in increasing children's motivation to pray in congregation at the mosque.